P155 Use of mycophenolate mofetil and azathioprine in patients with chronic hypersensitivity pneumonitis. (15th November 2017) - Fiddler, CA; Simler, N; Thillai, M; Parfrey, H
Abstract : Background: The optimal pharmacological management of chronic hypersensitivity pneumonitis (cHP) is unknown. Corticosteroids are often used as first line therapy but can be associated with side effects. There is a paucity of data examining the roln DLCO but not FVC (Morisset J et al. Chest. 2017). We aimed to determine the effece of steroid-sparing agents in cHP. A recent retrospective study demonstrated that treatment with either mycophenolate mofetil (MMF) or azathioprine (AZA) was associated with improvements it of MMF and AZA on lung function and prednisolone dose in cHP patients. Methods: Patients initiated on either MMF or AZA following a MDT diagnosis of cHP were retrospectively identified from the ILD service Papworth Hospital, Cambridge. Changes in lung function in the 9–12 months before and after treatment initiation were analysed. Daily prednisolone dose at initiation and 9–12 months treatment was recorded. Results: Twenty eight patients were identified between 2008 and 2016; 20 were treated with MMF (1–2 g daily) and 8 with AZA (25–150 mg daily). The mean age at drug initiation was 59.6±1.7 years and 61% were female. The mean duration from diagnosis to commencing MMF or AZA was 30.9±5.5 months. Twenty patients remained on either drug at 9–12 months and were include in the effectiveness analysis (FVC and TLCO data were available for 20 and 13 patients respectively). Five patients discontinued treatment due to drug side effects. Treatment with either MMF or AZA resulted in a significant reduction in prednisolone dose from 16.1±2.1 mg to 8.0±0.8 mg (p<0.001). MMF or AZA treatment for 9–12 months was associated with a significant improvement in TLCO (−0.62±0.3 vs+0.32±0.17 mmol/kPa/min, p<0.05). Although treatment reduced rate of FVC decline (−100±65 vs −30±66 mls), it was not significant (p=0.4). Conclusions: In our cohort of cHP, treatment with either MMF or AZA was associated with an improvement in TLCO consistent with findings of a previous retrospective study. Moreover, the addition of MMF or AZA enabled a significant reduction in prednisolone dose.